2022
DOI: 10.3390/plants11202676
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptomics for Genes Related to Berberine and Berbamine Biosynthesis in Berberidaceae

Abstract: Berberine and berbamine are bioactive compounds of benzylisoquinoline alkaloids (BIAs) present in Berberis species. The contents of berbamine are 20 times higher than berberine in leaf tissues in three closely related species: Berberis koreana, B. thunbergii and B. amurensis. This is the first report on the quantification of berberine compared to the berbamine in the Berberis species. Comparative transcriptome analyses were carried out with mRNAs from the leaf tissues of the three-species. The comparison of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…BIA biosynthesis starts with the condensation of dopamine and 4-hydroxyphenylacetaldehyde, both derived from L -tyrosine, to become ( S )-norcoclaurine, which then undergoes enzyme-mediated stepwise reactions including oxidation, reduction, methylation, acetylation, and decarboxylation, resulting in structural changes in the molecules [ 35 ]. The biosynthetic steps and enzymes have been well elucidated in the Coptis species [ 26 ], Berberis species [ 21 , 36 ], and other plants [ 34 ]. We identified all biosynthetic enzymes for berberine synthesis in the transcriptomes of C. robustum .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…BIA biosynthesis starts with the condensation of dopamine and 4-hydroxyphenylacetaldehyde, both derived from L -tyrosine, to become ( S )-norcoclaurine, which then undergoes enzyme-mediated stepwise reactions including oxidation, reduction, methylation, acetylation, and decarboxylation, resulting in structural changes in the molecules [ 35 ]. The biosynthetic steps and enzymes have been well elucidated in the Coptis species [ 26 ], Berberis species [ 21 , 36 ], and other plants [ 34 ]. We identified all biosynthetic enzymes for berberine synthesis in the transcriptomes of C. robustum .…”
Section: Discussionmentioning
confidence: 99%
“…We also isolated berberine synthesis genes from the transcriptomes in the NCBI database in other berberine-producing plants, which revealed that the copy numbers of each enzyme-encoding gene were highly variable in each species. The copy numbers of the berberine synthesis genes were also variable among the three closely related species in the genus Berberis [ 36 ]. In contrast to our results, half of the genes identified in the BIA synthesis were identical copies between Coptis teeta and C. chinensis [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations